Volume 7: Turbomachinery, Parts A, B, and C 2010
DOI: 10.1115/gt2010-22006
|View full text |Cite
|
Sign up to set email alerts
|

The Performance of a Generic Non-Axisymmetric End Wall in a Single Stage, Rotating Turbine at On and Off-Design Conditions

Abstract: The application of non-axisymmetric end walls in turbine stages has gained wide spread acceptance as a means to improve the performance of turbines in both power generation and aero-derivative applications. Non-axisymmetric end walls are aimed at the control of secondary flows and to a large extent have been developed through the use of computational fluid dynamics and detailed measurements in linear and annular cascades and proven in full scale engine tests. Little or no literature is available describing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
0
12
2
Order By: Relevance
“…Dunn et al (4) found a similar change in the tip leakage flow, but again it could not be explained. The numerical results show that the tip flow was not affected by the contour This is contrary to the numerical work presented in Sneddenet al (15) which uses the same grid and solution settings.…”
Section: Resultscontrasting
confidence: 86%
See 1 more Smart Citation
“…Dunn et al (4) found a similar change in the tip leakage flow, but again it could not be explained. The numerical results show that the tip flow was not affected by the contour This is contrary to the numerical work presented in Sneddenet al (15) which uses the same grid and solution settings.…”
Section: Resultscontrasting
confidence: 86%
“…Snedden et al (15) observed that the tip leakage flow was also affected but was not able to comment as to the cause of the change. Dunn et al (4) found a similar change in the tip leakage flow, but again it could not be explained.…”
Section: Resultsmentioning
confidence: 98%
“…The reason for large overturning is the high positive incidence at the rotor leading edge. Positive effects of the suppression of overturning at the hub area were mentioned by Snedden et al 6 This explains why the performance of the rotor decreases at low operating conditions. Yasa et al 3 found that with a low rotational speed, the importance of the rotor incidence is higher than the stator exit losses.…”
Section: Stator Flow Fields At Different Operating Conditionsmentioning
confidence: 88%
“…Five-hole probe measurements followed the methodology of Ingram and Gregory-Smith (25) . Unlike previous results (26,27) , the current investigation was performed with five pressure transducers for the 5-hole probe, as opposed to the four transducers as used previously. This additional transducer allows for a more accurate measurement of the static pressure in sheared flow.…”
Section: Experimental Set Upmentioning
confidence: 99%